Progenitor mass and ejecta asymmetry of supernova 2023ixf from nebular spectroscopy - Ferrari, Lucía; Folatelli, Gastón; Ertini, Keila; Kuncarayakti, Hanindyo; Andrews, Jennifer E. (EDP Sciences, 2025)
Context. Supernova (SN) 2023ixf was discovered in the galaxy M 101 in May 2023. Its proximity provided the scientific community an extremely valuable opportunity to study the characteristics of the SN and its progenitor. A point source detected on archival images and hydrodynamical modeling of the bolometric light curve have been used to constrain the former star’s properties. There is a significant variation in the published results regarding the initial mass of the progenitor. Nebular spectroscopy can be used to enhance our understanding of the SN and its progenitor.
Aims. We determined the SN progenitor mass by studying the first published nebular spectrum, taken 259 days after the explosion.
Methods. We analyzed the nebular spectrum taken with GMOS at the Gemini North Telescope. We identified typical emission lines, such as [O I], Hα, and [Ca II], among others. Some species’ line profiles show broad and narrow components, indicating two ejecta velocities and an asymmetric ejecta. We inferred the progenitor mass of SN 2023ixf by comparing its spectra with synthetic spectra and by measuring the forbidden oxygen doublet flux.
Results. Based on the flux ratio and the direct comparison with spectra models, the progenitor star of SN 2023ixf had a MZAMS between 12 and 15 M⊙. We find that using the [O I] doublet flux provides a less tight constraint on the progenitor mass. Our results agree with those from hydrodynamical modeling of the early light curve and pre-explosion image estimates that point to a relatively low-mass progenitor.